Sustainable optimization in the supply chain of an agroindustrial SME integrating lean green and circular economy to enhance waste valorization - Garate Colonia, Javier Sebastian (2024)
Currently, the agro-industrial sector is facing various issues. Among these are the imminent increase in food consumption caused by expected population growth, important levels of waste across all supply chain phases, and a lack of awareness regarding environmental care and resource utilization. Consequently, Peruvian SMEs in the sector are further affected due to their low competitiveness, a lack of culture of continuous improvement, and the prevalent business informality. To address this issue, the research proposes a model for improvement based on Circular Economy principles and the use of Lean Green for resource management. The proposal involves reusing process waste to produce biogas and fertilizers, aiming to enhance company performance and profitability. This involves considering technical, social, environmental, and economic aspects through strategic partnerships between the company and livestock farmers to acquire the necessary products. This strategy allows the company to enter new markets while producing clean energy that contributes to environmental conservation. The obtained results include a conversion factor from vegetable waste in kilograms to biogas, defined within a normal distribution with a mean of 0.3152 m³/kg VS and a standard deviation of 0.1295 m³/kg VS. For the economic evaluation of the biodigester installation, a Net Present Value of S/. 58.2k is estimated at the end of the fifth year of the project. This accounts for the sale of biol and fertilizer obtained from digestion, alongside an electric coverage of approximately 1.5 months/year through biogas conversion to kW in a generator.